MEDICINAL BIOMAGNETISM FOR PAIN RELIEF IN VASCULAR ALTERATIONS - APPLICATION OF STATIC MAGNETIC FIELDS THROUGH THE PROTOCOL FOR BLOOD FLOW IN LOWER LIMBS - Fabiana Pavanello, Eluza; Azevedo Canhas, Heloisa; Bravo Alba, Ivani; Sabina Michels, Otília; Lúcia Bosqueiro Capeleti, Vera; Mara Rambo Martini, Angela; Viapiana Bossa, Adriane (Health and Society, 2023)
Introduction: Chronic Venous Insufficiency (CVI) is a set of clinical manifestations resulting from the chronic dysfunction of the peripheral venous system that affects the lower limbs. There is a growing search for complementary therapies, such as Medicinal Biomagnetism (MB), which acts in a non-invasive, painless, low-cost and with rare contraindications, aiming to improve quality of life. MB uses Static Magnetic Fields (SMF) to restore bioenergetic balance and promote health, including CVI. Objective: The aim of this study is to evaluate the effect of SMF application, through the MB Lower Limb Blood Flow Protocol (LLBFP), on pain resulting from vascular alterations of the lower limbs. Methodology: This is a cross-sectional clinical experimental study in three female participants with vascular alterations in the lower limbs who underwent the LLBFP Protocol. Pain, edema and quality of life complaints were assessed using the Venous Insufficiency Epidemiological and Economic Study (VEINES), Visual Analogue Scale (VAS), and perimeter measurements questionnaires, before and after the application of the LLBFP. Results: After treatment with the LLBFP Protocol, there was a trend towards the analgesic effect and reduction of edema, as well as improvement in the aspects related to the symptoms of heavy, restless, tired legs, and tingling, burning and itching, promoting improvement in quality of life. Conclusion: This study demonstrated that the application of the MB LLBFP Protocol has the potential to reduce the subjective perception of pain and edema in lower limbs with vascular alterations. The magnets used in the LLBFP may promote an anti-inflammatory response, contributing to the improvement of quality of life.